RELATED PARTY TRANSACTIONS AS A MODERATOR OF THE EFFECT OF INVESTMENT DECISIONS ON FIRM VALUE - Ubaidillah, Moh.; Marsadena, Risna (Yayasan Nuraini Ibrahim Mandiri, 2025)
A decrease in company value needs to be considered because it has an impact on decreasing interest in buying shares and public interest in buying their products. The purpose of this study was to determine the effect of related party transactions on firm value with investment decisions as a moderating variable. This research method uses a quantitative approach using secondary data on manufacturing companies. The research population is manufacturing companies listed on the IDX in 2020-2023, totalling 165 companies. The data collection method uses perposive sampling which results in 75 company samples with 300 processed financial data. The analysis technique uses linear regression with SPSS version 24. The results of this study indicate that Related Party Transactions have a significant negative effect on firm value. Investment decisions have a significant positive effect on firm value. Furthermore, Related Party Transactions are able to moderate the effect of investment decisions on firm value in a significant positive manner. Keywords: Related Party Transaction, Investment Decisions, Firm Value